2002
DOI: 10.2307/3078855
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Comparative Data: A Test and Review of Evidence

Abstract: The question is often raised whether it is statistically necessary to control for phylogenetic associations in comparative studies. To investigate this question, we explore the use of a measure of phylogenetic correlation, lambda, introduced by Pagel (1999), that normally varies between 0 (phylogenetic independence) and 1 (species' traits covary in direct proportion to their shared evolutionary history). Simulations show lambda to be a statistically powerful index for measuring whether data exhibit phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
833
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(852 citation statements)
references
References 0 publications
15
833
3
1
Order By: Relevance
“…There has been considerable debate about when phylogenetic correction is important and which method to use (e.g., Freckleton et al 2002), but the lack of strong phylogenetic eVect we see here suggests that phylogenetic control is not a crucial issue for this study (see Results, Table 1). The phylogeny used was the same as for Cohen et al (2008a); methods of construction can be found there, and the phylogeny is available in supplementary material as shown in Newick format (S1).…”
Section: Full Data Setmentioning
confidence: 60%
“…There has been considerable debate about when phylogenetic correction is important and which method to use (e.g., Freckleton et al 2002), but the lack of strong phylogenetic eVect we see here suggests that phylogenetic control is not a crucial issue for this study (see Results, Table 1). The phylogeny used was the same as for Cohen et al (2008a); methods of construction can be found there, and the phylogeny is available in supplementary material as shown in Newick format (S1).…”
Section: Full Data Setmentioning
confidence: 60%
“…While PGLS allows for the fitting of several different evolutionary models while performing the regression, these models explain phylogenetic signal in the residuals (the fit of the tree to the regression) and do not relate directly to the test of whether the variables are significantly correlated (Freckleton et al. 2002; Revell 2010). …”
Section: Methodsmentioning
confidence: 99%
“…To control for the phylogenetic relationship among the sampled species, we used phylogenetic generalized least square regression (PGLS) models as implemented in the R statistical environment, using the libraries ape, MASS and mvtnorm and the function pglm3.3.r (see Díaz et al 2013 for a similar approach). After testing whether the phylogenetic scaling parameter lambda (λ) differs from 0 (phylogenetic independence; Freckleton et al 2002), we calculated the phylogenetically corrected correlation between the variables of interest after adjusting for phylogenetic effects through the estimated λ (see Díaz et al 2013 for a similar approach and the R script).…”
Section: Statistical Analysesmentioning
confidence: 99%